VERIFIKASI BERKAS DALAM PENCAIRAN DANA SANTUNAN KORBAN MENINGGAL DUNIA PADA PT JASA RAHARJA (PERSERO) KANTOR CABANG SUKABUMI - Liansah, Seli; Hermawan, Irwan (Jurnal Akuntansi AKTIVA, 2026)
This study aims to analyze the process of verifying documents in the disbursement of compensation funds for victims of global traffic accidents resulting in fatalities at PT Jasa Raharja (Persero) Sukabumi Branch Office. The study uses a narrative method with a qualitative approach. Data collection was conducted through observations during practical work activities, interviews with relevant officers, and documentation studies of compensation claim files. The results of the study indicate that the completeness and validity of claim files are primary factors determining the smooth disbursement of compensation funds. The process of verifying documents is carried out to ensure the truth of the accident incident, the validity of the victim's characteristics, and the legitimacy of the heirs entitled to receive compensation. All claim documents must be declared complete and in line with applicable provisions before the disbursement of funds is carried out. However, in its implementation, obstacles are still found in the form of incomplete files and limited access to the victim's location, which have the potential to disrupt the compensation fund disbursement process.